Exploring the coping strategies used by South African Hindu mothers to manage work-family conflict - Harrilal, Sohana (Organisational Psychology, 2021)
This study explored the experiences of employed South African Hindu mothers. The purpose of the exploration was to better understand the coping strategies that these mothers used to deal with their work and family role expectations. South African Hindu mothers are a subset of people who originate from traditional or collectivistic, cultural backgrounds, yet, live in a society in which workplaces subscribe to mainly, Western business practices. By exploring the coping strategies of this collectivistic cultural group in South Africa, the implications are relevant to what is known about coping with work and family demands. Secondary analysis of qualitative data led to the findings of this research. Twenty, unstructured, in-depth interviews allowed participants to share their stories as they wanted. From these stories, findings were that South African Hindu mothers used internal psychological processes, and, external processes to cope with their family and work demands. Internal processes included, reappraisal, ideals on duty, guilt, gratitude and acceptance. External processes included coping by externalising feelings, being supported by others, and, planning and organising. The research considers the influence of cultural norms and traditions juxtaposed by a modern way of living in relation to coping with the demands of work and family expectations. Future studies may benefit from building knowledge on how collectivism shapes coping and what is known about coping for additional, collectivistic cultural groups, particularly, within the South African context